5(7x-8)-4x=-6x-3

Simple and best practice solution for 5(7x-8)-4x=-6x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(7x-8)-4x=-6x-3 equation:


Simplifying
5(7x + -8) + -4x = -6x + -3

Reorder the terms:
5(-8 + 7x) + -4x = -6x + -3
(-8 * 5 + 7x * 5) + -4x = -6x + -3
(-40 + 35x) + -4x = -6x + -3

Combine like terms: 35x + -4x = 31x
-40 + 31x = -6x + -3

Reorder the terms:
-40 + 31x = -3 + -6x

Solving
-40 + 31x = -3 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
-40 + 31x + 6x = -3 + -6x + 6x

Combine like terms: 31x + 6x = 37x
-40 + 37x = -3 + -6x + 6x

Combine like terms: -6x + 6x = 0
-40 + 37x = -3 + 0
-40 + 37x = -3

Add '40' to each side of the equation.
-40 + 40 + 37x = -3 + 40

Combine like terms: -40 + 40 = 0
0 + 37x = -3 + 40
37x = -3 + 40

Combine like terms: -3 + 40 = 37
37x = 37

Divide each side by '37'.
x = 1

Simplifying
x = 1

See similar equations:

| 3z-12=12+7z | | 34-8x=2x-8(-2+2x) | | 40-8n=-8(1+4n) | | =s^3+4s^2+6 | | 8+5(6-3p)=-16-6p | | 6(-3x+1)-5x=-39-8x | | 10(3x+1+2)=34 | | 2*1r=4 | | 2x^2-40x-144=0 | | 6(5+x)-4x=24+5x | | 36-3m=-5(2m-3) | | -2n-8(-3n+4)=40+4n | | -n+3=-7(n+3) | | Tnr=pv | | 5x+3x+2x=3x+1 | | ax-c=borx | | 22+r=-(6-8r) | | 1-10y=27-3y+6 | | 5x-100+2x-25=75 | | 2x(3+y)=12 | | -20+4a=8(6-8a) | | 6(3+4x)-4=158 | | -(8x+8)-5=-8-3x | | -4n-21=-(-6-n)-2 | | 4x^2+3x+0=0 | | 81y^2-8=13 | | -32+5a=-8(a+6)+3 | | 3a-2a-a+11= | | .2x+3=8.6 | | 0=-3x^2+9x+9 | | 3(1-4b)=-6b+33 | | 28-7x=7x-6(2+4x) |

Equations solver categories